Aplikasi Alat Perangkat Pemipil Jagung Sebagai Upaya Menambah Pendapatan Petani Jagung Bagi Masyarakat Untuk Desa Pematang Kasih Kecamatan Pantai Cermin - Suhardi Napid; Khairul Suhada; Rahmat Rizaldi; Fikriansyah (Jurnal Masyarakat Indonesia (Jumas), 2024)
The Student Creativity Program (PKM) aims to increase the income of corn farmers in Pematang Kasih Village, Pantai Cermin District, through the introduction and application of corn threshing tools. The background of this activity is the low productivity of corn farmers caused by the threshing process which is still done manually, so it takes a lot of time and energy. Through this activity, socialization, training, and distribution of corn threshing tools to local farmers are carried out. The methods used in this activity include designing and making machines, theory and lectures, and training in using the tools. For a corn harvest of 1 hectare, if the corn cobs from the corn harvest are sold to collectors by corn farmers in the amount of 1 ton with the price provision from the collector of Rp. 3,100 / kg, then the funds obtained are Rp. 3,100,000. With the acquisition of Rp. 3,100,000, corn farmers have made a profit including the cost of jetting the land, buying seeds and fertilizers, spraying pests. The use of corn threshing tools will certainly make corn farmers experience even greater profits after drying the corn that is ready to be sold for Rp. 6,500/kg to each animal feed store with the consequence of having land for drying. The results of the activity show that the use of corn shellers can increase the efficiency of the shelling process by up to 70% and significantly increase farmers' income ≥75% including operational costs. In addition, this activity also improves farmers' skills in utilizing modern agricultural technology. Thus, this PKM activity is expected to be a model for empowering rural communities through technology, which not only improves farmers' welfare but also contributes to local economic development.